Exploring the Social and Economic Implications of Talaq in Islamic Law - Nafi’ah, Himmaty Alimatun; Fahmi, Chairul; Tarantang, Jefry (Antmind Review: Journal of Sharia and Legal Ethics, 2024)
This literature research aims to conduct an in-depth review of the literature and academic studies that discuss aspects of talaq in Sharia law, particularly emphasizing the phenomenological understanding of the social implications of worship involved in the talaq process. This research adopts a descriptive-analytical approach to literary sources, including scientific journals, books, articles, and related publications covering various viewpoints on talaq in the context of sharia law. Critical analysis identifies and analyzes views, viewpoints, and emerging issues concerning women's rights in the talaq process. The results of this study outline the diverse perspectives, approaches, and controversies that exist in talaq-related literature while highlighting the need for further emphasis on aspects of women's rights protection, empowerment, and efforts to achieve social justice in the context of sharia law.